Detection of a novel catalase in extracts of Mycobacterium avium and Mycobacterium intracellulare. - Wayne, L G (1988)
A novel class of catalase, which differs from the previously described M- and T-catalases of mycobacteria, was detected in strains of Mycobacterium avium and M. intracellulare. Designated A-catalase, this enzyme resisted inactivation at 68 degrees C, was inactivated by 3-amino-1,2,4-triazole (aminotriazole), and exhibited no peroxidase activity. All of these properties distinguished the enzyme from T-catalase. The A-catalase exhibited a Km of 70 mM H2O2, which is between the upper and lower extremes of the ranges reported for T- and M-catalases, respectively. The A-catalase appeared to be more hydrophobic than M-catalase and did not react with antiserum to a representative sample of this class. The banding patterns of T- and M-catalases seen by polyacrylamide gel electrophoresis (PAGE) were essentially unaffected by the incorporation of sodium dodecyl sulfate (SDS) into the PAGE system, whereas the single band of A-catalase seen by PAGE without SDS resolved into as many as five bands in the presence of SDS; these bands were all of slower mobility than the original band. The banding pattern seen with SDS appeared to be related more to counterion charge effects than to molecular size increases that could be attributed to SDS complexed to the protein. It remains to be determined whether the multiple A-catalase bands reflect different proteins or different SDS micellar complexes of a single protein.